2010
DOI: 10.1016/j.sdentj.2010.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of P53 protein in odontogenic cysts

Abstract: The p53 is a well-known tumor suppressor gene, the mutations of which are closely related to the decreased differentiation of cells. Findings of studies on immunohistochemical P53 expression in odontogenic cysts are controversial. The present study was carried-out to investigate the immunohistochemical expression of P53 protein in odontogenic cysts. Thirty paraffin blocks of diagnosed odontogenic cysts were processed to determine the immunohistochemical expression of P53 protein. Nine of the 11 odontogenic ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…A região posterior da mandíbula foi o sítio mais frequentemente encontrado neste estudo, resultado semelhante às pesquisas realizadas anteriormente, (GABALLAH;TAWFIK, 2010;CHAISUPARAT et al, 2013;JAMSHIDI;ZARGARAN;NAZHVANI, 2017). provavelmente por estar associado ao grande número de terceiros molares impactados nessa localização anatômica.…”
Section: Discussionunclassified
“…A região posterior da mandíbula foi o sítio mais frequentemente encontrado neste estudo, resultado semelhante às pesquisas realizadas anteriormente, (GABALLAH;TAWFIK, 2010;CHAISUPARAT et al, 2013;JAMSHIDI;ZARGARAN;NAZHVANI, 2017). provavelmente por estar associado ao grande número de terceiros molares impactados nessa localização anatômica.…”
Section: Discussionunclassified
“…The findings of the present study were in accordance with these authors as well as with the various other studies present in the literature. [20,26,27,32] Recent studies have also indicated that p53 alteration occurs at a greater frequency in invasive than in noninvasive carcinomas. [15,33] The high reactivity of p53 protein in OKCs …”
Section: Discussionmentioning
confidence: 99%
“…40 These results are also supported by other studies. 41 Nevertheless it was also reported that p53 protein is only detectable in KOTs among the jaw cysts along with a higher PCNA existence dentigerous or radicular cysts compared to KOTs. 42 Öktemer, reports higher expression of this marker may help us explain the aggressive course of KOT in comparison to other odontogenic cysts.…”
Section: Ki-67mentioning
confidence: 98%